Electric-Driven Polarization Meta-Optics for Tunable Edge-Enhanced Images - Cheng Cheng; Kai Ou; Hui Yang; Hengyi Wan; Zeyong Wei; Zhanshan Wang; Xinbin Cheng (Micromachines, 2022)
In this study, we demonstrate an electrically driven, polarization-controlled metadevice to achieve tunable edge-enhanced images. The metadevice was elaborately designed by integrating single-layer metalens with a liquid-crystal plate to control the incident polarization. By modulating electric-driven voltages applied on the liquid-crystal plate, the metalens can provide two polarization-dependent phase profiles (hyperbolic phase and focusing spiral phase). Therefore, the metalens can perform two-dimensional focusing and spatial differential operation on an incident optical field, allowing dynamic switching between the bright-field imaging and the edge-enhanced imaging. Capitalizing on the compactness and dynamic tuning of the proposed metadevice, our scheme carves a promising path to image processing and biomedical imaging technology.